UERJ Robotics Team's Educational Project - Alves, Alan Ribeiro; Albuquerque, Theo De Quadros; Revoredo, Teo Cerqueira (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
The educational robotics project at UERJ was cre-ated in 2018 aiming at democratizing access to technological knowledge, connecting universities and public schools. It is intended to awaken the interest of children and adolescents in robotics by promoting stimulating challenges while strengthening the bond between school and students with a more interesting environment. The project's scope encompasses development of expository and practical content, including printed and digital teaching materials, as well as educational videos, participation in educational fairs and school visits to universities and other places, inspiring students to consider robotics as a possibility of a professional career. Despite the challenges, the project has made significant progress in promoting children's cognitive and creative development, contributing to a more knowledgeable society.